Snow-melting performance of building waste heat: An experimental evaluation - Suzuki Yosuke; Terasaki Hiroaki; Jia Ziyi; An Xinyi; Nakayama Hiroshi; Onishi Yoshimasa; Nishihara Yoshiki (E3S Web of Conferences)
This study experimentally investigated the performance of a snow-melting system using waste heat from a building at the Matsunokitouge parking area in Takayama City, Gifu Prefecture. Accordingly, snowmelt on the interlocking blocks (ILBs) proceeded rapidly under ventilation conditions with an average main pipe air temperature of 17 °C and an airflow rate of 51.5 m3/m2h when the outside air temperature was approximately -2°C or higher, and the hourly snow intensity was 2.0 cm/h or less. Furthermore, a temperature difference of approximately 4°C was observed between the air exiting the joints and the ILB surface. Hence, snow accumulation on the joints was minimal when the hourly snowfall rate was below 4.0 cm/h. In addition, the ILB surface in the snowmelt area remained ice-free even under icy conditions, such as an air temperature of -15°C, effectively preventing falls caused by road surface freezing.